Duplication of Vertebral Pedicles Associated with a Thoracic Burst Fracture Resulting in Spinal Cord Compression: A Case Report - Johnson, Ryan (Cureus, 2019)
Vertebral body fractures are well-known sources of axial back pain with the potential to cause neurological deficits. Duplication of a component of the vertebral column is a rare phenomenon; however, vertebral pedicle duplication is an unreported phenomenon, and has not been reported in association with a vertebral burst fracture and kyphotic deformity. We present a unique case of vertebral pedicle duplication in association with a T11 vertebral burst fracture in a 72-year-old female. In addition to her risk factors, it is the belief of the authors that the anatomic anomaly increased the segmental kyphosis at the level of the T11 vertebral body, thereby increasing the axial load on that segment, and increasing the risk for fracture.